PERAN GURU TERHADAP PENCEGAHAN PERILAKU KEKERASAN DI SEKOLAH SMP NEGERI I KUTA MALAKA ACEH BESAR - Ambia Nurdin; Ricky Dear Fitria (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The role of the teacher relates to how a teacher is able to understand and determine the limits that must be done in organizing material, interacting and doing the learning process. Violent behavior is the use of force or force with the aim of hurting a weaker person or group so that the victim feels depressed or traumatized and helpless. This study aims to determine the role of teachers in preventing violent behavior in SMP Negeri I Kuta Malaka Aceh Besar. This research is descriptive with a cross-sectional study approach through the total sampling technique. Research data collection was carried out on 5 to 7 December 2019 in SMP Negeri I Kuta Malaka Aceh Besar with a total of 28 respondents, data collection tools used in the form of a questionnaire scale consisting of 20 question items. Data analysis is presented in the form of a frequency distribution table. The results showed that 64.3% had a teacher's role as a corrector for the prevention of violent behavior in schools, 60.7% had a teacher's role as an informer for the prevention of violent behavior in schools, 78.6% had a teacher's role as a class manager for preventing violent behavior in schools. Based on these data, there is a teacher's role in preventing violent behavior in schools, so the researchers suggest maintaining a good role in providing guidance to students at school